2021
DOI: 10.3390/antiox10030469
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-Gallate Plus Omega-3 Restores the Mitochondrial Complex I and F0F1-ATP Synthase Activities in PBMCs of Young Children with Down Syndrome: A Pilot Study of Safety and Efficacy

Abstract: Down syndrome (DS) is a major genetic cause of intellectual disability. DS pathogenesis has not been fully elucidated, and no specific pharmacological therapy is available. DYRK1A overexpression, oxidative stress and mitochondrial dysfunction were described in trisomy 21. Epigallocatechin-3-gallate (EGCG) is a multimodal nutraceutical with antioxidant properties. EGCG inhibits DYRK1A overexpression and corrects DS mitochondrial dysfunction in vitro. The present study explores safety profiles in DS children age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…When the mitochondrial respiratory chain is not operative, it is the main producer of ROS. It has consequences in biogenesis, structure, dynamics, and metabolism of the mitochondrial of T21, which subsequently is associated with neurogenesis and neuroplasticity impairment [ 85 ]. In experiments using EGCG in cultured fibroblasts and lymphoblasts from DS patients, Valenti and his colleagues have been able to show a protective effect on mitochondrial energy deficit and oxidative stress by lessening mitochondrial energy damage.…”
Section: Down Syndrome and Catechinsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the mitochondrial respiratory chain is not operative, it is the main producer of ROS. It has consequences in biogenesis, structure, dynamics, and metabolism of the mitochondrial of T21, which subsequently is associated with neurogenesis and neuroplasticity impairment [ 85 ]. In experiments using EGCG in cultured fibroblasts and lymphoblasts from DS patients, Valenti and his colleagues have been able to show a protective effect on mitochondrial energy deficit and oxidative stress by lessening mitochondrial energy damage.…”
Section: Down Syndrome and Catechinsmentioning
confidence: 99%
“…These in vitro findings can also be related to another in vivo study, Scala and coworkers have shown that in DS children aged between 1 and 8 years, a treatment of decaffeinated EGCG enriched by omega-3 for 6 months ensues the repairing of the deficit of mitochondrial complex I and ATP synthase. Moreover, they give evidence about the safety of EGCG in children without side effects in hepatic, renal, and thyroid function [ 85 ].…”
Section: Down Syndrome and Catechinsmentioning
confidence: 99%
“…It has also been demonstrated that EGCG exerts a positive effect on cognitive function by promoting ROS scavenging ( Schroeder et al, 2009 ) and counteracting the Aβ-induced mitochondrial apoptotic processes ( Fukutomi et al, 2021 ). Importantly, it has recently been reported that EGCG treatment ameliorates mitochondrial respiration deficits in children affected by Down syndrome ( Scala et al, 2021 ). A recent meta-analysis of 17 studies performed on animal models of AD has demonstrated that EGCG can rescue cognitive impairment and Aβ pathology through the combination of its anti-inflammatory, antioxidant, and antiaggregating activities ( Zhang et al, 2020 ).…”
Section: Plant-derived Natural Compounds As Multi-target Disease-modi...mentioning
confidence: 99%
“…Furthermore, Vacca & Valenti letter describe a trial in their letter, consisting of only two participants; one child with DS as a treatment group, whereas the younger brother served as a control. In a more recent publication the same group looked into the safety of EGCG and omega-3 in a pilot study with 20 DS children of 0-8 years old and they concluded it can be safely administered under medical supervision in DS children [115].…”
Section: Is There a Theoretical Basis In The Literature Why Children With Down Syndrome Would Need Dietary Supplements?mentioning
confidence: 99%